Long-term consequences of the Chornobyl disaster for aquatic ecosystems: A retrospective analysis and prognosis - R. Makhinko (Екологічна безпека та збалансоване ресурсокористування)
Radioactive contamination of aquatic ecosystems as a result of anthropogenic disasters poses a serious threat to the environment and human health. The purpose of the study was to comprehensively analyse the long-term consequences of the Chornobyl disaster for aquatic ecosystems. The methodology included retrospective data analysis, field research, laboratory experiments, and mathematical modelling. The retrospective analysis covered historical data from 1986; field studies included sampling of water, sediments, and biota; laboratory experiments focused on studying the effects of radiation on aquatic organisms; mathematical modelling allowed predicting long-term trends. Changes in aquatic biocoenoses for the period 1986-2024 were analysed. The dynamics of concentrations of basic radionuclides 137Cs, 90Sr, and 241Am in components of aquatic ecosystems, migration processes of radionuclides in the aquatic environment, and their bioaccumulation in organisms of various trophic levels was investigated. Special attention was paid to the impact of chronic radiation pollution on biodiversity, productivity, and genetic structure of aquatic populations. Changes in the species composition and number of key groups of hydrobionts were analysed. Based on long-term data and modern models, forecasts have been developed for the further development of the radioecological situation in the aquatic ecosystems of the exclusion zone until 2070-2090. A set of innovative measures to minimise negative consequences was proposed, including the use of nanotechnologies, genetically modified organisms, and automated monitoring systems. The need for international cooperation and the creation of a global database for long-term management of polluted aquatic ecosystems was substantiated. The results of the study are important for developing strategies for environmental management of radioactively contaminated areas and preparedness for possible future radiation incidents